2021
DOI: 10.3390/ani11020428
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Responses of Wild Rodents to Owl Calls in an Austral Temperate Forest

Abstract: Ecologically based rodent management strategies are arising as a sustainable approach to rodent control, allowing us to preserve biodiversity while safeguarding human economic activities. Despite predator signals being known to generally repel rodents, few field-based studies have compared the behavioral effects of several predators on different prey species, especially in Neotropical ecosystems. Here, we used camera traps to study the behavior of rodent species native to the Chilean temperate forest (Abrothri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…Similarly, Mori et al (2020) showed that the wild boar increases its nocturnality and reduces diurnal activity in areas where a high frequency of wolf passage was recorded. Our findings showing that wild boars are less active during very bright nights, lead us to interpret this behaviour as an anti-predatory strategy, similar to moonlight avoidance in small mammals (Viviano et al 2020;Hernández et al 2021). Thus, where hunting occurs, where predation pressure is high, or in suburban and urban areas, the onset of wild boar activity is usually recorded at sunset (Cahill et al 2003;Mori et al 2020;Rossa et al 2021), whereas in protected areas and where predators are rare, it may occur some hours before (Russo et al 1997;Podgórski et al 2013;Zanni et al 2021).…”
Section: Discussionmentioning
confidence: 65%
“…Similarly, Mori et al (2020) showed that the wild boar increases its nocturnality and reduces diurnal activity in areas where a high frequency of wolf passage was recorded. Our findings showing that wild boars are less active during very bright nights, lead us to interpret this behaviour as an anti-predatory strategy, similar to moonlight avoidance in small mammals (Viviano et al 2020;Hernández et al 2021). Thus, where hunting occurs, where predation pressure is high, or in suburban and urban areas, the onset of wild boar activity is usually recorded at sunset (Cahill et al 2003;Mori et al 2020;Rossa et al 2021), whereas in protected areas and where predators are rare, it may occur some hours before (Russo et al 1997;Podgórski et al 2013;Zanni et al 2021).…”
Section: Discussionmentioning
confidence: 65%
“…Javan slow loris is thus more affected by the increased predation risk (predation risk hypothesis [16]) than by the increased foraging efficiency and detection of predators (visual acuity hypothesis [16]). Lunarphobia is a common strategy to reduce predation risk in other small and medium-sized nocturnal mammals [16][17][18]37].…”
Section: Discussionmentioning
confidence: 99%
“…Moon luminosity is a major masking factor influencing the activity of mammals as it is directly linked to increased predation risk, but also to a higher visibility of food or prey [15,16]. Prey species thus often reduce their activity levels during bright nights (i.e., lunarphobia), although they can also adapt the strategy to increase their activity levels during bright nights to increase their potential to spot predators and have the additional advantage of maximizing their foraging efficiency (i.e., lunarphilia) [17,18]. Predators are thus usually lunarphilic if they are at the high end of the food chain [19], although there are cases when predators can adapt to their prey and entrain their activity pattern to match that of their favored prey [20].…”
Section: Introductionmentioning
confidence: 99%
“…In the first phase, capturability was higher than the post treatment, which could be because traps were novel objects and O. longicaudatus could have been exploring these devices to assess their risks [ 67 , 68 , 69 ]. O. longicaudatus is considered a scansorial species [ 70 ] but it frequently forages on the ground and explores novel sources of food [ 71 ]. They possess a remarkable jumping ability and partial bipedalism, which allow them to escape quickly from predators when they are foraging on the ground [ 72 , 73 ].…”
Section: Discussionmentioning
confidence: 99%